1998
DOI: 10.1002/(sici)1097-4695(199810)37:1<146::aid-neu11>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium regulation of channel and receptor expression in the plasmalemma: Potential sites of sensitivity along the pathways linking transcription, translation, and insertion

Abstract: Nervous system development is “activity dependent”—activation of neurons controls their development, which controls their activation patterns, which will then influence their further development, and so on. A critical issue is thus the regulation of channel and receptor expression. For nerve cells, the presence of specialized Ca2+‐permeable channels in the surface membrane provides a direct link between electrical activity and the intracellular Ca2+ ion concentration ([Ca2+]i), and in many instances [Ca2+]i is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…An important readout signal appears to be intracellular [Ca 2+ ], which correlates with electrical activity due to voltage-dependent Ca 2+ channels and buffering mechanisms that average out fluctuations in time and space (Berridge 1998; Wheeler et al, 2012). Moreover, long-term changes in [Ca 2+ ] are found to regulate many ion channel types (Barish 1998; Mermelstein et al, 2000; O’Leary et al, 2010; Turrigiano et al, 1994; Wheeler et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…An important readout signal appears to be intracellular [Ca 2+ ], which correlates with electrical activity due to voltage-dependent Ca 2+ channels and buffering mechanisms that average out fluctuations in time and space (Berridge 1998; Wheeler et al, 2012). Moreover, long-term changes in [Ca 2+ ] are found to regulate many ion channel types (Barish 1998; Mermelstein et al, 2000; O’Leary et al, 2010; Turrigiano et al, 1994; Wheeler et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…While our study characterizes which parameter configurations are energy efficient, we did not study the mechanisms of how biological circuits would modulate their conductances in order to arrive at these configurations. Long-term changes in intracellular calcium have been found to regulate many ion channels ( 53 55 ); thus, it is possible that intracellular calcium is used to tune conductances for energy efficiency. In our study, we found that intracellular calcium level is linearly related to energy consumption across circuit configurations that match experimental data ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These homeostatic mechanisms maintain [Ca 2+ ] i at low levels, usually about 100 nM in neurons compared to an extracellular concentration of approximately 1 mM. Maintaining [Ca 2+ ] i at such low levels in the cell allows relatively small or localized increases in [Ca 2+ ] i to be used as a trigger to activate signal transduction pathways which lead to physiological processes such as activation of specific enzymes or modulation of ion channels (Racay and Lehotsky, 1996; Tymianski and Tator, 1996; Barish, 1998; Weber, 2004). …”
Section: Mechanisms Of Maintaining Calcium Homeostasis In Neuronsmentioning
confidence: 99%
“…An individual neuron may have several different types of VGCCs and ROCs, and Ca 2+ influx through specific channels is quite important. For example, certain classes of VGCCs trigger neurotransmitter release at synaptic terminals (Robitaille et al, 1990; Augustine et al, 1991; Robitaille et al, 1993; Wu et al, 1998), and specific ionotropic glutamate receptors can lead to Ca 2+ -dependent gene induction (Bading et al, 1993; Lerea and McNamara, 1993; Barish, 1998). …”
Section: Mechanisms Of Maintaining Calcium Homeostasis In Neuronsmentioning
confidence: 99%